1966
DOI: 10.1099/00221287-43-3-411
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Resistance of Bacterial Spores at Various Water Activities

Abstract: SUMMARYThe heat resistance of the spores of six species of bacteria varied with water activity (a,) at which the spores were heated, although the magnitude of the changes differed greatly between species. At all a, values there was an approximately linear relation between the logarithm of the number of viable spores and the time of heating. The slopes of these straight lines were used to describe the observed death-rates as the time ( D value) required to decrease the population by one log. unit. For all six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(47 citation statements)
references
References 3 publications
5
42
0
Order By: Relevance
“…As far as we know, there is no reported study on the effect of CO 2 treatment on the inactivation ratio (approximately 5-log-cycle) of G. stearothermophilus in a food system. Spore heat inactivation decreases in proportion to the decrease of water activity of the spore suspension medium (Alderton, Chen, & Ito, 1980;Harnulv et al, 1977;Mazas et al, 1999;Murrell & Scott, 1965). In our experiments suspension addition of glucose, sodium chloride and ethanol decrease water activity of the solution.…”
Section: Resultsmentioning
confidence: 86%
“…As far as we know, there is no reported study on the effect of CO 2 treatment on the inactivation ratio (approximately 5-log-cycle) of G. stearothermophilus in a food system. Spore heat inactivation decreases in proportion to the decrease of water activity of the spore suspension medium (Alderton, Chen, & Ito, 1980;Harnulv et al, 1977;Mazas et al, 1999;Murrell & Scott, 1965). In our experiments suspension addition of glucose, sodium chloride and ethanol decrease water activity of the solution.…”
Section: Resultsmentioning
confidence: 86%
“…Wet heat resistance is the ability for spores to survive high temperatures when suspended in an aqueous solution (Setlow, 2006). This property is a universal characteristic of bacterial spores, but differences in heat tolerance between Bacillus and other spore-forming species have been noted (Murrell and Scott, 1966; Setlow, 2014). While B. subtilis spores can easily survive exposure to 80°C (Milhaud and Balassa, 1973; Setlow, 2006; Leggett et al, 2012), previous studies in C. difficile have demonstrated that C. difficile spores are comparatively wet heat-labile (Lawley et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In general, spore heat resistance is greatest at low aw values (0.2 to 0.4) and lowest as the aw approaches 1.0 (63). Several studies have revealed the impact of salt on spore heat resistance.…”
Section: Total Reduction Of Hazard Lrmentioning
confidence: 96%